2015
DOI: 10.1001/jama.2015.88
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corticosteroids on Treatment Failure Among Hospitalized Patients With Severe Community-Acquired Pneumonia and High Inflammatory Response

Abstract: IMPORTANCE In patients with severe community-acquired pneumonia, treatment failure is associated with excessive inflammatory response and worse outcomes. Corticosteroids may modulate cytokine release in these patients, but the benefit of this adjunctive therapy remains controversial. OBJECTIVE To assess the effect of corticosteroids in patients with severe communityacquired pneumonia and high associated inflammatory response. DESIGN, SETTING, AND PARTICIPANTS Multicenter, randomized, double-blind, placebo-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
301
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 452 publications
(316 citation statements)
references
References 39 publications
8
301
1
6
Order By: Relevance
“…A recently published RCT on the role of systemic corticosteroids among patients hospitalized for community-acquired pneumonia with high inflammatory response has indicated a protective effect of corticosteroids. 47 This paradoxical beneficial effect of corticosteroids that has been earlier suggested 15, 46 might be further supported by the higher adherence among ICS users in RCTs. A sensitivity analysis by PP strategy, which accounted for the imbalance in drop-out rates in RCTs, showed that patients in ICS arms had significantly decreased unadjusted overall mortality compared to patients in non-ICS arms.…”
Section: Discussionmentioning
confidence: 90%
“…A recently published RCT on the role of systemic corticosteroids among patients hospitalized for community-acquired pneumonia with high inflammatory response has indicated a protective effect of corticosteroids. 47 This paradoxical beneficial effect of corticosteroids that has been earlier suggested 15, 46 might be further supported by the higher adherence among ICS users in RCTs. A sensitivity analysis by PP strategy, which accounted for the imbalance in drop-out rates in RCTs, showed that patients in ICS arms had significantly decreased unadjusted overall mortality compared to patients in non-ICS arms.…”
Section: Discussionmentioning
confidence: 90%
“…This assessment of baseline microvascular status could be based upon bedside intravital microscopy (with its accompanying technical limitations) or systemic markers of endothelial damage (with their accompanying logistic concerns as point-of-care tests). The promise of such personalized approaches to infection treatment has been demonstrated in recent studies of pneumonia, in which a benefit of adjunctive corticosteroids existed largely in patients with baseline evidence of systemic inflammation 120,121 .…”
Section: Novel Microcirculation-protective Therapiesmentioning
confidence: 99%
“…Community-acquired pneumonia (CAP) and influenza infections together are the fourth most prevalent cause of death worldwide (3). The morbidity, mortality, and costs associated with CAP have remained unchanged in recent decades, despite availability of antibiotic treatments and preventive strategies with immunizations (4,5).…”
Section: Introductionmentioning
confidence: 99%